Analisis Profil Berpikir Kritis, Kreatif, Keterampilan Kolaboratif, dan Literasi Lingkungan Siswa Kelas 8 SMP Muhammadiyah sebagai Impak Pembelajaran Modern - Nurwidodo, Nurwidodo; Romdaniyah, Sri Wulan; Sudarmanto, Sudarmanto; Rosanti, Dina; Kurniawati, Kurniawati; Abidin, Zaenal (Bioscientist : Jurnal Ilmiah Biologi, 2021)
This study aims to determine the initial profile of critical thinking, creative thinking, collaborative skills and environmental literacy as the impact of the implementation of modern learning. Modern learning in this study includes STEAM, Collaborative and EMKONTAN learning. This research is a descriptive analytic study conducted on 8th grade students of SMP Muhammadiyah 2 Batu City. The research population was all students of SMP Muhammadiyah 2 Batu City. The sampling technique was purposive sampling, using 8th grade students as research samples. The instruments used are critical thinking tests, creative thinking tests, collaborative observation sheets and environmental literacy questionnaires. Data analysis used quantitative and qualitative descriptive analysis. The results showed that the students’ critical thinking profile on the five indicators was in the very good category. The ability to think creatively shows that the flexibility indicator has a higher average value than the other 3 indicators. Collaborative skills indicators show that the indicators of productive work and compromise are 80.13 in the very good category, the environmental literacy profile shows that the average knowledge indicator is 71.08 in the good category, the cognitive skills indicators are 67.95 in the good category, attitude is 76.13 with good category, responsible environmental behavior indicator with good number is 66.88 with good category. The results of data analysis show that the four profiles have good and very good categories. There is an increase in the profile of critical thinking skills, creative, collaborative skills and environmental literacy in the second cycle of learning for all implemented learning models. There is a significant relationship between creative thinking skills and STEM learning processes and outcomes. There is a significant relationship between collaborative skills with STEM learning processes and outcomes. It can be concluded that the implementation of modern learning produces a good and very good profile of critical thinking, creative, collaborative and environmental literacy.